Caisson Foundations for Competitive Offshore wind Farms in ITALY. (2016) - Govoni, Laura; Gottardi, Guido; Antonini, Alessandro; Archetti, Renata; Schweizer, Joerg
Abstract: The research presented in the paper moves from the results of a feasibility study recently carried out for the development of an offshore wind farm off the cost of Rimini, in the Northern Adriatic Sea. The work, based on in-situ measurements of the environmental conditions, assessed the suitability of the considered area for the development of a relatively large wind farm, although at the profitability limit. The study has considered 60 offshore wind turbines installed on monopiles, as they are, at present, the most common solution and a quantification of the investment costs could be reliably completed. With reference to such case, the paper addresses the use of caisson foundations, a convenient alternative to monopiles in water of shallow to intermediate depth, with the final aim of improving the overall cost-effectiveness of the investment.